2011
DOI: 10.1002/jbm.a.33191
|View full text |Cite
|
Sign up to set email alerts
|

Modification of poly(ether urethane) with fluorinated phosphorylcholine polyurethane for improvement of the blood compatibility

Abstract: In order to improve the blood compatibility, poly(ether urethane) (PEU) and fluorinated phosphorylcholine polyurethane (P-HFPC) were used to prepare PU/P-HFPC blends by solution mixing. The hemocompatibility in vitro was evaluated with protein adsorption and platelet-rich plasma (PRP) contact tests. It was found that the amount of adsorbed protein on surface was decreased by 87%, and almost no platelet adhesion and activation was observed on the surface of blends when P-HFPC content was above 5 wt %. After add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
(65 reference statements)
0
18
0
Order By: Relevance
“…22 Covalent binding of fibronectin 23 or RGD peptides 24,25 as well as a laminin-nonapeptide 26 improved integrin-mediated cell adhesion of endothelial cells or progenitor cells. Other strategies such as binding of anticoagulants like heparin, 27 phosphorylcholine, 28 or Argatroban 29 pursued the aim to reduce platelet adhesion, activation and aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…22 Covalent binding of fibronectin 23 or RGD peptides 24,25 as well as a laminin-nonapeptide 26 improved integrin-mediated cell adhesion of endothelial cells or progenitor cells. Other strategies such as binding of anticoagulants like heparin, 27 phosphorylcholine, 28 or Argatroban 29 pursued the aim to reduce platelet adhesion, activation and aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a series of PUs containing fluorinated alkyl phosphatidylcholine (PC) side groups have been prepared in our group, of which the fluorinated side chain could help PC polar headgroup directly connected migration onto PU surfaces leading to relatively good hemocompatibility for PUs 18–21. In addition, these fluorinated phospholipid polyurethanes (FPCPUs) as blending additives could effectively improve surface properties and hemocompatibility of PUs 22, 23. However, it was found that the mimicking biomembrane surfaces of the PUs forming by fluorocarbon single‐chain PC could not properly suppress protein adsorption, for example, the inhibitory rate of fibrinogen (Fg) adsorption onto these fluorinated PC poly(carbonate urethane)s surfaces compared with that onto pristine poly(carbonate urethane)s surfaces was only to about 75%, similarly ascribed to the unstable self‐assemble structures of the fluorocarbon single‐chain PC 18, 24.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the use of small molecules that combine fluoroalkyl and PC moieties simultaneously could address this challenge as it has been shown with low density polyethylene . In this sense, the concept of such SMMs provided a promising strategy since fluorinated alkyl chains can direct the biomimetic phosphatidylcholine moieties toward the surface and simultaneously limit water uptake given the fluorine chemistry's inherent hydrophobicity . Examples of these systems are described in Table .…”
Section: Smms Based On Fluorinated Oligomersmentioning
confidence: 99%
“…The addition of further oligomer did not show any improvement in blood contact character. This was consistent with the XPS results where no changes in phosphorous or fluorine concentration were observed on the surface for concentrations higher than 5% …”
Section: Smms Based On Fluorinated Oligomersmentioning
confidence: 99%